IMPLEMENTASI PERAWATAN LUKA MODERN DI RS HARAPAN MAGELANG - -, Rohmayanti; Kamal, Sodiq (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
Wound management is an important part in wound management of patients at the Hospital. In practice wound management is often overlooked by less applying knowledge continues to evolve today. Latest wound management is the principle of moist, which is conditioned wounds covered and accompanied bandage application by using a drug that can accelerate wound healing. This study was using descriptive approach. Subject were nurses who have worked in Hospital and interest with woundcare and selected by purposive sampling. The analysis data using univariate and bivariate. This devotion is done in Harapan Hospital by conducting seminar and workshop latest wound care, followed by practice on direct patient with injuries for a month. These activities are carried out in the span of two months implemented in the Harapan Hospital. The number of participants is 50 people during the workshop and 25 people on the presentation case. Results of this activity is an increase in knowledge and skills of nurses on the latest wound care and changing policies at the Hospital with special room as a wound care clinic by using the principles of modern wound care.Keywords: implementation, modern wound care